2022
DOI: 10.3390/nu14122434
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of East Asian Herbal Medicine for Inflammatory Skin Lesions in Plaque Psoriasis: A Systematic Review, Meta-Analysis, and Exploration of Core Herbal Materials

Abstract: Psoriasis is an inflammatory autoimmune skin disease with various clinical manifestations. The aim of this review was to systematically evaluate the efficacy and safety of oral administration of East Asian herbal medicine (EAHM) for inflammatory skin lesions in psoriasis and to explore core herbal materials for drug discovery. A comprehensive search was conducted in 10 electronic databases for randomized controlled trials from their inception until 29 July 2021. Statistical analysis was performed in R version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…The above results can be compared to previous studies we have conducted. Previously, we analyzed data from clinical trials comparing the efficacy of CM with the oral administration of EAHM alone and explored the core herbal materials through frequency analysis and network analysis [ 215 ]. In that study, EAHM showed superiority in PASI 70, PASI 60, and continuous PASI scores compared to the CM group.…”
Section: Discussionmentioning
confidence: 99%
“…The above results can be compared to previous studies we have conducted. Previously, we analyzed data from clinical trials comparing the efficacy of CM with the oral administration of EAHM alone and explored the core herbal materials through frequency analysis and network analysis [ 215 ]. In that study, EAHM showed superiority in PASI 70, PASI 60, and continuous PASI scores compared to the CM group.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The researchers also conducted some SRs and meta-analyses to evaluate the efficacy and safety of EAHM for primary cancer pain, autism spectrum disorder, rheumatoid arthritis, and psoriasis. 9 , 45 , 46 At the same time, this team applied the association rule mining to identify core herb combination based on the collected data, to provide a methodological reference for our study. Interestingly, our study will use sensitivity analysis to mine herbal combinations.…”
Section: Discussionmentioning
confidence: 99%
“…EAHM refers to natural materials used as medicines to treat diseases in East Asia, based on theories of syndrome differentiation and treatment, which include traditional Chinese herbal medicine (CHM), Korean herbal medicine (KHM) and Japanese Kampo medicine (KM). 9 EAHM provide comprehensive approaches to NSCLC therapies, 10 and have gradually become a huge resource base for developing anticancer drugs. 11 - 13 EAHM have the unique advantages of synergism, attenuation of cancer treatment, comprehensive palliative treatment, 14 alleviation of treatment-related symptoms, and improvement in the overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of evidence on the efficacy and safety of Chinese Herbal Medicine has already been established through previous studies. 23 Notably, resveratrol, prevalent in red grapes and wine, exhibits antioxidative and anti-inflammatory attributes. 24 Curcumin, derived from turmeric, is renowned for its potent anti-inflammatory and antioxidant effects, often necessitating strategies to enhance its bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Given this, it becomes sense to assume that TwHF’s underlying mechanism involves a multicomponent, multi-targeted action that modifies the immune system and the systemic inflammatory state linked to the symptoms of psoriasis. 23
Figure 2 Structural formula of chemical components isolated from Tripterygium wilfordii Hook. F .
…”
Section: Introductionmentioning
confidence: 99%